2021
DOI: 10.3389/fcimb.2021.770759
|View full text |Cite
|
Sign up to set email alerts
|

EhVps23: A Component of ESCRT-I That Participates in Vesicular Trafficking and Phagocytosis of Entamoeba histolytica

Abstract: The endosomal sorting complex required for transport (ESCRT) is formed by ESCRT-0, ESCRT-I, ESCRT-II, ESCRT-III complexes, and accessory proteins. It conducts vesicular trafficking in eukaryotes through the formation of vesicles and membrane fission and fusion events. The trophozoites of Entamoeba histolytica, the protozoan responsible for human amoebiasis, presents an active membrane movement in basal state that increases during phagocytosis and tissue invasion. ESCRT-III complex has a pivotal role during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(46 citation statements)
references
References 73 publications
3
42
1
Order By: Relevance
“…This protozoan causes human amoebiasis, affecting 50 million ( Bercu et al., 2007 ) and killing 100,000 individuals around the world each year ( World Health Organization, 1997 ). In our efforts to understand the molecular basis of the aggressive mechanism of the trophozoites, we have studied proteins of the endosomal sorting complexes required for transport (ESCRT) ( Avalos-Padilla et al., 2015 ; Avalos-Padilla et al., 2018 ; Galindo et al., 2021 ), and others associated that cooperate in molecular trafficking and virulence events of this parasite ( Lopez-Reyes et al., 2010 ; Bañuelos et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This protozoan causes human amoebiasis, affecting 50 million ( Bercu et al., 2007 ) and killing 100,000 individuals around the world each year ( World Health Organization, 1997 ). In our efforts to understand the molecular basis of the aggressive mechanism of the trophozoites, we have studied proteins of the endosomal sorting complexes required for transport (ESCRT) ( Avalos-Padilla et al., 2015 ; Avalos-Padilla et al., 2018 ; Galindo et al., 2021 ), and others associated that cooperate in molecular trafficking and virulence events of this parasite ( Lopez-Reyes et al., 2010 ; Bañuelos et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We know that the E. histolytica ESCRT machinery possesses at least 19 genes ( Lopez-Reyes et al., 2010 ), whose products act in several steps of endosomal sorting, vesicular trafficking and phagocytosis ( Lopez-Reyes et al., 2010 ; Bañuelos et al., 2012 ; Avalos-Padilla et al., 2015 ; Avalos-Padilla et al., 2018 ; Galindo et al., 2021 ). So far, we have found that the ESCRT-III complex ( Avalos-Padilla et al., 2015 ; Avalos-Padilla et al., 2018 ) proteins work together and with the EhADH protein, an ALIX family member ( Bañuelos et al., 2012 ), and the EhVps4 ATPase ( Lopez-Reyes et al., 2010 ), the enzyme required to maintain the cycle of binding and release of ESCRT-III proteins from the endosomal membranes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations